Análisis jurídico de casos de violencia intrafamiliar denunciadas en la junta cantonal de la defensa de los derechos de la ciudad de Ibarra en el año 2020 - Arellano Ponce, Génesis Paulina (2024)
This research is titled 'Legal analysis of cases of domestic violence reported to the Cantonal Board for the Defense of Rights of the city of Ibarra in 2020', which analyzes the international and national legislation that protects the rights of children. , girls and adolescents\; identifies the powers of the Cantonal Board for the Protection of Rights and evaluates the effectiveness of its administrative procedure through compliance with the protection measures dictated in the resolutions of said entity. The general objective of this work is to determine how effective the Cantonal Board for the Protection of Rights was in fulfilling its public function of defending the rights of girls, boys and adolescents in the incidence of cases of violence against women and members of the core. family members registered in 2020. The question that drives the investigation is: Is the Cantonal Board for the Protection of Rights effective in fulfilling its public function of defending the rights of girls, boys and adolescents in the incidence of cases of violence against the woman and members of the family nucleus registered in 2020? The research approach is qualitative and the methods applied were normativist and socio-legal, since legal regulations and interviews with members of the Cantonal Board for the Protection of Rights of Ibarra were analyzed. The results of thisinvestigation revealed that in said entity only 61.25% of compliance and effectiveness of the protection measures granted in favor of the rights of girls, boys and adolescents who have been victims of domestic violence in said canton during the year 2020.